Usposabljanje za andragoško delo - Đorđević, Neda (Vzgoja in izobraževanje, 2012)
Professionals at Slovenian Institute for Adult Education within the educational activities dedicate much attention to training and networking of adult education workers and ultimately adult educators from all over Slovenia.The development of our programmes is influenced by several factors, most important is certainly the direction of ACS in the development and research, as it allows us to develop new models and forms of learning which contribute to knowledge transfer in the types of professionals and training organizations and to increase the impact of practice on development and research in the field of adult education. Further, we present summary analysis of participants' satisfaction with training in 2010.
Keywords: additional training of adult educators; adult education; andragogika; Andragoški center Slovenije; andragoško spopolnjevanje; further education of teachers; in-service adult education and training; izobraževanje odraslih; izpopolnjevanje učiteljev; Slovenian Institute for Adult Education; vseživljenjsko učenje